A novel COL6A2 mutation causing late-onset limb-girdle muscular dystrophy - Manu Jokela; Sara Lehtinen; Johanna Palmio; Anna-Maija Saukkonen; Sanna Huovinen; Anna Vihola; Bjarne Udd (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2022)
Limb-girdle muscular dystrophies (LGMD) are genetic disorders characterized by weakness of predominantly proximal limb and trunk muscles due to progressive loss of muscle tissue. Collagen VI-related muscular dystrophies usually display more generalized muscle involvement combined with contractures and/or hyperlaxity of distal finger joints. LGMD-like phenotype of collagenopathy has only rarely been described and as reported is usually of childhood onset. We identified a Finnish family with COL6A2-related LGMD with autosomal dominant inheritance and very late onset at 40–60 years of age. Since the mutation was previously unreported, the pathognomonic findings on muscle MRI were the decisive clue for the correct diagnosis.